The COVID-19 Pandemic and Health and Care Workers: Findings From a Systematic Review and Meta-Analysis (2020-2021) - Mandana Gholami; Iman Fawad; Sidra Shadan; Rashed Rowaiee; HedaietAllah Ghanem; Amar Hassan Khamis; Samuel B. Ho; Samuel B. Ho (Frontiers Media S.A., 2023)
Objectives: The COVID-19 pandemic has greatly impacted health and care workers (HCW) globally, whom are considered at greater risk of infection and death. This study aims to document emerging evidence on disease prevalence, clinical outcomes, and vaccination rates of HCWs.Methods: Three databases were surveyed resulting on 108 final articles between July-December 2020 (period 1) and January-June 2021 (period 2).Results: Amongst the overall 980,000 HCWs identified, in period 1, the estimates were 6.1% (95% CI, 4.1-8.8) for the PCR positivity rate. Regarding outcomes, the hospitalization prevalence was 1.6% (95% CI, 0.7-3.9), and mortality rate of 0.3% (95% CI, 0.1-0.8). In period 2, the PCR positivity rate was 8.1% (95% CI, 4.6-13.8). Analysis of outcomes revealed a hospitalization rate of 0.7% (95% CI 0.3-1.8), and average mortality rate of 0.3% (95% CI 0.1-0.9). Our analysis indicated a HCW vaccination rate of 59.0% (95% CI, 39.4-76.1).Conclusion: Studies from the latter half of 2020 to the first half of 2021 showed a slight increasing trend in PCR positivity among HCW, along with improved clinical outcomes in the 1-year period of exposure. These results correlate well with the improving uptake of COVID-19 vaccination globally.